Hermon Carey Bumpus, Yankee Naturalist - Bumpus, Hermon Carey, 1888-1977 (Book collections on Project MUSE., 1947)
Hermon Carey Bumpus, Yankee Naturalist was first published in 1947. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. In this small volume, Dr. Bumpus' son has outlined the personal history and professional career of his distinguished father, who will be known to countless associates through his work with American museums, and his outstanding career as educator and administrator: as director of the Marine Biological Laboratory at Woods Hole, Massachusetts; as professor of biology at Brown University; as the first director of the American Museum of Natural History; as business manager of the University of Wisconsin; as president of Tufts College; and as chairman of the advisory board of the National Park Service. The trailside museums and natural history shrines that have taught thousands of Americans the story behind the scenic and natural wonders of our national parks are an enduring memorial to this man of enthusiasm and unceasing energy. The habitat exhibits in our museums of natural history bear further witness to the imagination and practical originality of this distinguished American naturalist, who was the first president of the American Association of Museums and who contributed so much to the change of attitude and policy at a time when museums of every type were just thawing out of their ice age.